Keefektifan Group Counseling - Person Centered (GC-PC) untuk Meningkatkan Penyesuaian Diri Santri di Pesantren Walyatalaththof Darussalam - Fa’izah Nurul Hidayati; Akhmad Fajar Prasetya (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
The purpose of this study was to measure the effectiveness of group counseling services using the Individual-Oriented approach in supporting students to adapt at the Walyatalaththof Darussalam Kebumen Islamic Boarding School. The type of research applied in this study was a quantitative approach with a pre-experimental design research method through pretest and posttest in one group. This study was a pre-experimental design with a pretest-posttest design in one group to determine the results of the treatment more precisely because it can be compared with the conditions before the treatment was given. The subjects of the study were class VII students of PP Walyatalaththof Darussalam Kebumen, namely 6 students who had low self-adjustment criteria. The study was conducted in 8 sessions, each for 40 minutes. The researcher collected data by utilizing a self-adjustment scale. Based on the results of the research analysis, it was obtained that, (1) Before participating in group counseling with a person-centered approach, the Subjects got an average score of 60.66, which was included in the